IMPLEMENTASI ALGORITMA APRIORI UNTUK ANALISA PEMILIHAN TIPE GENRE FILM ANIME (STUDI KASUS : MYANIMELIST.NET) - Azis, Mochammad Abdul; Hadianto, Nur; Miharja, Jaja; Rifai, Saifulloh (LPPM Universitas Nusa Mandiri, 2018)
As with Japanese animated films or can also be called an anime film which is now starting to be popular with all circles regardless of age, status and profession. In Japanese anime films, it has several genres from action, comedy, drama, romance, adventure, etc., can be accessed as in online media such as websites that offer various types of anime, one of which is myanimelist.net on this web having 14,000 anime films shared genre. One way to increase the appeal of anime films is to use the genre data that is often watched by anime movie lovers. With these data we foam analyze what types of genres are the most watched, as wellas the tendency to choose alternative genre types that are liked by anime movie lovers. So with these data the creator can determine the strategy for the type of genre that will be created next. a priori algorithm is good for use for itemset formation, pattern searching and so on. Therefore in this study the a priori algorithm was used to determine the pattern of selection of genre types in Japanese Anime Films.